TESTING THE ANTIHYPERGLYCEMIC POTENTIAL OF THE ETHANOL EXTRACT OF PAPUAN ANTS' NESTS (Myrmecodia pendans) ON MENCIT (Mus musculus) - fania, vikafania; Hardia, Lukman; Astuti, Ratih Arum (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
The use of synthetic drugs has potential pose a risk of complications in sufferers of hyperglycemia. WHO recommends the use of traditional medicine to prevent & treat chronic diseases. The problem formulation includes the effectiveness of the original Papuan EESS test in treating hyperglycemia in mice, with a comparison of results at doses of 100.8 mg/kgBB, 50.4 mg/kgBB, and 25.2 mg/kgBB. This research aims to prove effectiveness of native Papuan EESS in treating hyperglycemia with mice & compare the effectiveness at different doses. The research uses an experimental laboratory design. Male mice aged 2 – 3 months with body weight of 20 – 30 grams, divided into five groups: control + glibenclamide 13.39 mg/kgBW, control - NaCMC 1%, native Papuan EESS treatment dose 100.8 mg/kgBW, 50.4 mg/kgBB, and 25.2 mg/kgBB. Alloxan 4.54 mg/kgBW was administered to create hyperglycemia in mice. Extraction used the maceration method with 70% ethanol solvent. The research results showed that EESS suspension was effective in treating hyperglycemia. The dose of 100.8 mg/kgBB had an average decrease in blood sugar of 122.17 mg/dL, higher than the dose of 50.4 mg/kgBB (decrease of 155.00 mg/dL) and 25.2 mg/kgBB (decrease 200.33mg/dL). In the control group, control + with 13.39 mg/kgBW glibenclamide showed a greater reduction (121.87 mg/dL) than control - with 1% NaCMC (205.83 mg/dL reduction). EESS is native to Papua antihyperglycemia is effective in mice with hyperglycemia. Comparison of the effectiveness of EESS doses showed a significant difference in response.